Object oriented Transcription Factors Database (ooTFD). - Ghosh, D (1999)
ooTFD is an object-oriented database for the representation of information pertaining to transcription factors, the proteins and biochemical entities which play a central role in the regulation of gene expression. Given the recent explosion of genome sequence information, and that a large percentage of proteins encoded by fully sequenced genomes fall into this category, information pertaining to this class of molecules may become an essential aspect of biology and of genomics in the 21st century. In the past year, there was a small increase in the size of this database, and a number of new tools to facilitate data access and analysis have been added at the MIRAGE (Molecular Informatics Resource for the Analysis of Gene Expression) web site. ooTFD and associated tools and resources can be accessed at http://www.ifti.org/